Class Struggle and Terrorism: How the political exclusion of the poor fostered social-revolutionary terrorism in the 19th and early 20th centuries - Daniel Meierrieks (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2022)
What is the link between the political exclusion of the poor and the emergence of anarchist and leftist terrorism in the 19th and early 20th centuries? In his contribution to the Online Mitteilungen, Daniel Meierrieks draws on historical data to show that the exclusion of the poor, the monopolization of political power by wealthy segments of the population, as well as class antagonism favored the emergence of a social-revolutionary terrorism, but not terrorism associated with other ideologies, such as extreme nationalism. There is a systematic link between the social forces that were dominant from the mid-19th century onward (e.g., urbanization, industrialization, and the emergence of the working class), social-revolutionary ideologies formulated in response to these developments (notably anarchism and Marxism), and political violence. Prior to this study, researchers had to rely mostly on anecdotal evidence to derive this link.
Keywords: 300